Large congenital nevus spilus-improved follow-up through the use of in vivo reflectance confocal microscopy - Christine Prodinger; Rafaella Tatarski; Martin Laimer; Verena Ahlgrimm-Siess (Mattioli1885, 2013)
Background: Nevus spilus (NS) is a potential precursor of melanoma; the vast majority of cases reported in the literature were histologically classified as superficial spreading melanoma. Objective: To demonstrate the diagnostic value of reflectance confocal microscopy (RCM) in this subtype of congenital nevi. Methods: We report a case of a large congenital NS with equivocal clinical and dermoscopic findings in which RCM was applied for diagnosis and follow-up. Results: There was a good correlation of RCM with histopathology and a lack of dynamic changes during follow-up. Conclusion: Our observations indicate that RCM, as a non-invasive tool, can be useful for diagnosis and follow-up of clinically and dermoscopically equivocal NS.